EFFECT OF SUPERIMPOSED DC AND AC ELECTRIC FIELDS ON WATER VAPOR CONDENSATION IN A CORONA REACTOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Humidity control in various rooms or installations, whether small or large, is a constant concern. Heat exchangers are generally used whose temperature is maintained below the dew point. Thus, water vapor condenses on the surface of these cooled elements, and the water can be extracted in liquid form. Energy efficiency and effective control of these installations are two critical aspects that are of constant interest in practical applications. This paper presents an experimental study on the condensation efficiency of water vapor in a cylindrical reactor with controlled temperature and corona discharges obtained with a wire electrode positioned on its central axis and supplied with a continuous positive or negative electric voltage. Thus, as a first step, the influence of corona discharges and the DC electric field on the efficiency of water vapor condensation is investigated. Secondly, the experimental study also explores the impact of an AC field superimposed over the DC field corresponding to the corona discharge. The obtained results indicate that the application of the AC electric field superimposed over the DC corona field significantly improves the condensation efficiency of water vapor.
Keywords: Humidity control; Corona discharge reactor; DC and AC electric fields